2009
DOI: 10.1007/s11010-009-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Egr-1 upregulates OPN through direct binding to its promoter and OPN upregulates Egr-1 via the ERK pathway

Abstract: Early growth response factor-1 (Egr-1) and osteopontin (OPN) play important roles in the migration and proliferation of vascular smooth muscle cells (VSMC), but little is known about their relationship. Therefore, we transfected VSMCs with either Egr-1 cDNA, Opn cDNA, a DNA enzyme designed to target Egr-1 (ED5), or antisense Opn oligodeoxynucleotides and examined changes in Egr-1 and OPN expression at the mRNA and protein levels. OPN expression levels were increased in cells that were stably transfected with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Our transient transfection experiments suggested that Egr1 and Egr2 mediate the activation of Osteopontin promoter by MEK-MAPK signaling in chondrocytes. Consistent with our observations, Egr1 has been shown to bind to the Osteopontin promoter in vascular smooth muscle cells (31) . Genetic studies in mice have also implicated Egr1 and Egr2 in the regulation of terminal chondrocyte differentiation (19,32) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our transient transfection experiments suggested that Egr1 and Egr2 mediate the activation of Osteopontin promoter by MEK-MAPK signaling in chondrocytes. Consistent with our observations, Egr1 has been shown to bind to the Osteopontin promoter in vascular smooth muscle cells (31) . Genetic studies in mice have also implicated Egr1 and Egr2 in the regulation of terminal chondrocyte differentiation (19,32) .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our observations, Egr1 has been shown to bind to the Osteopontin promoter in vascular smooth muscle cells. (31) Genetic studies in mice have also implicated Egr1 and Egr2 in the regulation of terminal chondrocyte differentiation. (19,32) Taken together, our observations suggest that MEK-MAPK signaling regulates chondrocyte terminal differentiation at least in part through Egr1 and Egr2.…”
Section: Discussionmentioning
confidence: 99%
“…b-Catenin has been considered a strong target for chemotherapeutical interventions, owing to its disruption in multiple cancers and its action as a proto-oncogenic TR in cultured cells. 18,28 Since FH535 was originally identified as a transcriptional inhibitor for b-catenin from a blind screen, the identification of nonspecific effects on b-catenin expression and EGR-1 was unsurprising, but insightful. 17 The work here with FH535 demonstrates that depletion of b-catenin from the cytoplasmic face through prolonged FH535 treatment was associated with disruption of tight junctions and acquisition of a mesenchymal cell shape.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple outcomes of FH535 and/or CSC treatment identified in these studies, including fibronectin and osteopontin, are transcriptional targets of EGR-1. 14,18 The EGR-1 accumulated in the nuclei following 24 hours of CSC, FH535 or combination CSC, FH535 treatment of BEAS-2B cells ( Figure 4A and B). The CSC induced a dose-dependent nuclear accumulation of EGR-1, which was accompanied by a similar dose-dependent increase in the EGR-1 target gene PTEN ( Figure 4C).…”
Section: Egr-1 Outcomes Are Altered By Csc and Fh535mentioning
confidence: 99%
“…OPN is a multifunctional cytokine that contributes to cell proliferation, survival, drug resistance, invasion, and stem cell behavior [24]. It has been documented that Egr1 upregulates OPN through direct binding to its promoter, and OPN upregulates Egr1 via the ERK pathway [25]. OPN has been linked to sustaining hematopoietic stem cell polarity and attenuating the aging of old hematopoietic stem cells [26].…”
Section: Introductionmentioning
confidence: 99%